Laparoscopically assisted percutaneous endoscopic gastrostomy performed for remnant stomach in patient with amyotrophic lateral sclerosis: a case report - Yutaro Ohgaki; Yuji Ishibashi; Fumihiko Hatao; Ryuichiro Furuta; Noriyuki Saito; Rie Inayoshi; Yasuhiro Morita (Surgical Case Reports, 2023)
Abstract Background Although percutaneous endoscopic gastrostomy (PEG) offers better access to the gastrointestinal system, in patients with previous abdominal surgery, PEG can be unsuccessful. Laparoscopically assisted percutaneous endoscopic gastrostomy (LAPEG) is indicated for such patients. However, patients with amyotrophic lateral sclerosis (ALS) may be more susceptible to anesthesia-related complications than other patients, requiring the indications for LAPEG, along with perioperative management, to be considered carefully. Case presentation A 70-year-old, male patient with ALS was referred to our hospital for a gastrostomy for progressive dysphagia. He had undergone an open distal gastrectomy for gastric ulcer perforation in his twenties. Upper gastrointestinal endoscopy denied the transillumination sign and focal finger invagination. Because the risk of respiratory complications caused by general anesthesia was not considered serious, the decision was made to perform a LAPEG. Under careful, intraoperative airway management and neuromuscular monitoring, adhesiolysis was performed to increase mobility of the remnant stomach. A gastrostomy tube was inserted through the abdominal wall and into the remnant stomach under laparoscopic and endoscopic guidance. The patient was discharged in stable condition on postoperative day 3 without any respiratory complications. Conclusions LAPEG was able to be performed in a patient with ALS with a previous gastrectomy. A perioperative team comprised of neurologists, endoscopists, surgeons, anesthesiologists, and nurses who are fully conversant with ALS must be assembled to deal with potentially complex medical issues related to the procedure and anesthetic and perioperative management.